Potensi Ekstrak Daun Manggrove Minyak (Rhizophora apiculata Blume) Asal Pesisir Kuala Langsa sebagai Anti Hiperglikemik pada Mencit yang Diinduksi Aloksan - Fazrina Zahara; Elisa Putri; Dewi Yuniharni; Ainan Nazirah (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2024)
This study aimed to determine the effect of ethanol extract from mangrove leaves (Rhizophora apiculata Blume.) on reducing blood glucose levels in alloxan-induced mice (Mus musculus L.). The method used was laboratory experimental research with a quasi-experimental design. Male mice (Mus musculus L.) were selected as samples based on Federer’s empirical formula using purposive sampling techniques. All mice were acclimated for seven days before treatment. Treatments were administered orally daily for 14 days. The results showed that ethanol extract of mangrove leaves significantly reduced blood glucose levels, with the highest effectiveness observed at doses of 100 mg/kgBW (75.1%), 200 mg/kgBW (58.6%), and 300 mg/kgBW (70.1%). Statistical analysis using One Way ANOVA indicated no significant differences (p < 0.05) between the three doses. In conclusion, ethanol extract from mangrove leaves (Rhizophora apiculata Blume.), which contains alkaloids, flavonoids, saponins, steroids, phenols, and tannins, is effective in reducing blood glucose levels. Among the three doses tested, the 200 mg/kgBW dose proved to be the most effective. Keywords: Alloxan, Antidiabetic, Mangrove Leaves